2018
DOI: 10.1021/acsaem.8b01597
|View full text |Cite
|
Sign up to set email alerts
|

Self-Steerable Propulsion of Disk-Like Micro-Craft with Dual Off-Center Nanoengines

Abstract: This paper reports a novel disk-like micro-craft with dual off-center nozzle nanoengines, consisting of three different metals: gold, nickel, and platinum. A bubble propulsion mechanism originating from momentum change induced by the detachment of oxygen bubbles is proposed to elaborate the self-steerable propulsion of the disk-like gold-nickel-platinum micro-craft. The asproposed micro-craft is fabricated by a layer-by-layer deposition method based on the microelectro-mechanical systems technology. Herein, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Mallouk et al demonstrated the internalization of a nanowire-based motor inside living cells, as shown in Figure 25D. Developing biocompatible materials and fuels for artificial micro-/ nanomotors or the use of noninvasive external triggered motors may pave the way for biomedical applications of micro-/nanomotors in the near future [72][73][74][75][76][77][78][79][80].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Mallouk et al demonstrated the internalization of a nanowire-based motor inside living cells, as shown in Figure 25D. Developing biocompatible materials and fuels for artificial micro-/ nanomotors or the use of noninvasive external triggered motors may pave the way for biomedical applications of micro-/nanomotors in the near future [72][73][74][75][76][77][78][79][80].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Such micromotors could be used for environmental remediation and practical applications. [28][29][30][31][32][33][34][35][36]…”
Section: Surfactant Effect On Au-ni-pt Micromotor's Propulsion and Ementioning
confidence: 99%
“…However, for gold nanohelices 400 nm high, 400 nm in diameter, and 80 nm thick nanowires, the chirality enhancement factor was determined as 10, so the use of such structures in biosensing is limited [75]. This problem was solved by fabricating superstructures with several nanohelices [76] using direct laser recording methods [77,78] or ion-and electron beam lithography [79][80][81]. The use of such structures made it possible to increase the optical chiral amplification factor up to two orders of magnitude and to adjust the CD signal from IR to the visible region of the spectrum.…”
Section: Biosensing With 3d Chiral Nanostructuresmentioning
confidence: 99%
“…The following review demonstrated the formation of chiral nanocrystals of Te and Se, which can be used as a matrix for growing nanostructures of gold and silver tellurides [87]. Also, there was presented the growth of chiral gold nanoparticles in the opposite direction induced by amino acids and peptides [77]. The effect of different growth rates on the chiral morphology of gold nanocrystals in the presence of L-Cys or D-Cys was observed.…”
Section: Biosensing With 3d Chiral Nanostructuresmentioning
confidence: 99%